The National Qualifications Framework in Austria: Zooming in to classification of learning outcome between common sense and curriculum theory - Schlögl, Peter [Verfasser] (My University, 2021)
“Since 2016 the law on the National Qualifications Framework (NQF) has been in force in Austria. In the meantime, as regulated by the law, qualifications have been assigned in various forms in individual procedures (with exception for the Bologna-compliant university certificates, who were once again able to achieve a special path for themselves). This also applies to both in-company and school-based vocational training, as well as certificates for continuing education. The assessment of the early phase of implementation suggests that learning outcome orientation is often confused with an efficient production process. The similarity in name between Frederik W. Taylor as an important representative of scientific management and Ralph W. Tyler as a bestselling author of early learning outcome orientation can be symbolic of the fuzziness, if not the conceptual confusion, which is evident in the implementation of the NQF in Austria. Namely, the insufficient separation of principles and instruments of curriculum development and presentation based on learning outcome. What had already been pointed out by the critical reception of the learning objectives model is currently being repeated in the debate on the classification of formal education in general education, vocational education and training, learning in universities and in continuing education against the background of the descriptors of the eight levels of the NQF, as well as in emphasizing the difference between qualifications determined by law and those in non-formal education. Although the current assessment is based on expert knowledge, it is nevertheless a common-sense level assessment with a superficial definition of educational theoretical goals based on historically established didactic models, some of which are centuries or decades old. However, it is evaluated if the pragmatic approach chosen in Austria, could lead to problems in the medium and long term. A benevolent but critical review of the first years of the implementation of the NQF in Austria.” (author’s abstract; BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; 370; EU-Bildungspolitik; Nationaler Qualifikationsrahmen; Lernergebnisorientierung; Österreich